PENGARUH CAPITAL INTENSITY, PROFITABILITY, DAN FIRM SIZE TERHADAP TAX AGGRESSIVENESS - Aprilin, Natashia Vania; Yuniarwati, Yuniarwati (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This study aims to analyze and empirically prove the effect of capital intensity, profitability, and firm size on tax aggressiveness in companies engaged in manufacturing listed on the Indonesia Stock Exchange in 2018-2020. Purposive sampling technique is the method used in this study. The total sample is 249 observational data obtained from the IDX financial statements. Data processing in this study uses the Eviews version 12 program. The results show that capital intensity has a positive and significant effect on tax aggressiveness, but profitability and firm size do not affect tax aggressiveness.